Agama Dan Ekonomi: Kemiskinan Di Indonesia Dalam Persfektif Karl Marx Tentang Agama Sebagai Alieanasi - Agustina, Dena (UIN Sunan Kalijaga Yogyakarta, 2022)
The purpose of this study is to discuss poverty in Indonesia based on Karl Marx's perspective on religion and alienation. It offers insightful ideas on that Karl Marx's theory of religion and Alienation is true. Many people are so dependent on religion that they continue to pray without trying. Religion seems to be an opiate where they can complain about reality. This research emphasizes that human life must be balanced between the life of the world and the hereafter.